Aplicações terapêuticas da Punica granatum L. (romã) - Werkman, C. [UNESP] (2008)
The therapeutic use of plants has wide popular acceptance and support by the World Health Organization, stimulating scientific research. This type of alternative therapy has been adopted to treat several diseases since it is cheap and easily accessible. Among potentially medicinal plants is Punica granatum L. (pomegranate). In literature, there are reports on pomegranate antimicrobial and anti-inflammatory activities, besides therapeutic actions in dentistry and medicine. This review describes several published experiments that demonstrate the many phytotherapic functions of this fruit.